2020
DOI: 10.1155/2020/4372603
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Supply Chains with Competing Manufacturers considering Fairness Concerns

Abstract: In this study, we examined the contract coordination between manufacturers with peer-induced and distributional fairness concerns. A revenue sharing contract was introduced to coordinate a competitive supply chain, in which the manufacturers have different fairness concerns based on centralized decision-making in terms of fairness neutrality. Then, we constructed two game models—the manufacturer’s peer-induced fairness concern model and the manufacturer’s distributional fairness concern model and analyzed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 31 publications
1
23
0
1
Order By: Relevance
“…Based on this, this study started from the perspective of enterprise management capabilities and explored the path to achieve the “win–win” goal of corporate environmental performance and financial performance under the intermediary transmission of enterprise environmental protection investment. In addition, existing research in China mainly uses the nature of enterprise property rights [ 12 ] and shareholding structure [ 13 ] as the moderating variables of the relationship between internal control quality and enterprise performance, or uses the enterprise social responsibility [ 14 ], agency costs [ 15 ], and overconfidence of management [ 16 ] as the intermediary variables. The above studies lack the practical needs based on the construction of ecological civilization and fail to organically link the three relationships by using enterprise environmental protection investment as an intermediary variable.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, this study started from the perspective of enterprise management capabilities and explored the path to achieve the “win–win” goal of corporate environmental performance and financial performance under the intermediary transmission of enterprise environmental protection investment. In addition, existing research in China mainly uses the nature of enterprise property rights [ 12 ] and shareholding structure [ 13 ] as the moderating variables of the relationship between internal control quality and enterprise performance, or uses the enterprise social responsibility [ 14 ], agency costs [ 15 ], and overconfidence of management [ 16 ] as the intermediary variables. The above studies lack the practical needs based on the construction of ecological civilization and fail to organically link the three relationships by using enterprise environmental protection investment as an intermediary variable.…”
Section: Introductionmentioning
confidence: 99%
“…Su et al [33] propose a cost profit-sharing contract to coordinate a closed-loop supply chain with third-party recycling, taking environmental protection factors into account. Jian et al [34] design a revenuesharing contract to coordinate a supply chain with competing manufacturers, considering the manufacturer's peer-induced fairness concern model and the manufacturer's distributional fairness concern model. Coordination of SC under cost information asymmetry has also attracted the attention of researchers.…”
Section: Sc Coordinationmentioning
confidence: 99%
“…Revenue-sharing contracts were used to resolve channel conflicts in dual-channel supply chains [31]. Jian et al [32] examined the contract coordination between manufacturers with peerinduced and distributional fairness concerns and found that there is a revenue-sharing contract parameter in both the peer-induced and distributional fairness concerns of manufacturers.…”
Section: Literature Reviewmentioning
confidence: 99%